Assessment of Information Literacy Skills of MD Medical Postgraduate Trainees in the electronic environment: a mixed method approach - Sritharan, T. (University of Colombo, 2022)
This study aimed at assessing the information literacy skills of MD medical postgraduate trainees in the electronic environment. The mixed method approach of both quantitative and qualitative was used and the population of this study was 815 MD medical postgraduate trainees in 32 medical specialties. Applying the ‘Lwanga and Lemeshow’ method 427 trainees were selected as sample. The questionnaire and the focus group discussions were the data collecting instruments. Data from the questionnaire was analyzed using SPSS ver. 23. QDA Miner lite was used to analyze the data from focus group discussions. Total number of 427 questionnaires were distributed and 380 of them responded at the rate of 89%. Thirty-two (32) participants from 32 medical specialties were invited for the focus group discussions. Findings revealed that 276 males and 104 females responded, respectively. The findings revealed that the majority of respondents (74.5%) required information to prepare them for examinations and 58.7% required information for publications. Out of total respondents, 16.6% and 15.8% stated that their computer and internet literacy were poor and very poor, respectively. Several suggestions were made by the respondents from focus group discussions regarding the training needs for enhancing electronic information literacy. Among them 48.4% stated that they have enough skills and 42.9% have requested for training on accessing electronic resources. However, 22.4% of PG trainees strongly agreed that they have no skills to access electronic resources thus it affects their PG medical education. More than 75% of the respondents highly stressed about the training on searching techniques to narrow down their search to get the most accurate and relevant resources, and to save their time. Based on the findings, study concluded that information literacy skills play a vital role in the use of electronic information resources and a proper training is needed in information literacy skills. Findings of the study recommend that the library of PGIM should provide proper training on information literacy skills and should enhance efficient Internet services in the library.
Keywords: Information literacy skills; electronic resources; Postgraduate medical trainees; Electronic environment